2010
DOI: 10.1371/journal.pone.0015120
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screen for Mycobacterium tuberculosis Genes That Regulate Host Immunity

Abstract: In spite of its highly immunogenic properties, Mycobacterium tuberculosis (Mtb) establishes persistent infection in otherwise healthy individuals, making it one of the most widespread and deadly human pathogens. Mtb's prolonged survival may reflect production of microbial factors that prevent even more vigorous immunity (quantitative effect) or that divert the immune response to a non-sterilizing mode (qualitative effect). Disruption of Mtb genes has produced a list of several dozen candidate immunomodulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 71 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…Under protocols approved by the Weill Cornell Medical College or Rockefeller University Institutional Animal Care and Use Committees, mice were infected by aerosol with ∼100 bacilli. Tissues were collected at time points and processed to enumerate cfu as described (17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under protocols approved by the Weill Cornell Medical College or Rockefeller University Institutional Animal Care and Use Committees, mice were infected by aerosol with ∼100 bacilli. Tissues were collected at time points and processed to enumerate cfu as described (17).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier work demonstrated that the transposon disrupting virR had inserted between codons 121 and 122 (17). However, it remained to be established whether the VirR protein was absent, truncated, or modified with a neo-C terminus, whether the mutant Significance Bacteria stimulate host cells in part via secreted products, some of which are packaged in membrane vesicles (MV).…”
Section: Virr Deficiency Augments Responses Of Mouse and Human Macropmentioning
confidence: 99%
See 1 more Smart Citation
“…However, relatively few gene products have been identified that directly attenuate innate immune cell functions (6,19,24,27,28,33,34,39,42,45). Several distinct approaches have been used to identify putative virulence factors, including transposon mutagenesis of M. tuberculosis, isolation and characterization of regions of difference (RD), and studies of eukaryotic-like proteins encoded by the M. tuberculosis genome.…”
Section: Discussionmentioning
confidence: 99%
“…This stable cell line provides a 40-fold range of GFP expression in every cell infected. Another report described the use of immunoreporter macrophage cell lines (6). In that case, the macrophages only provided transient reporter expression that had a wide fluorescence distribution.…”
Section: Discussionmentioning
confidence: 99%